Multifaceted regulation of the HOX cluster and its implications in oral cancer - Padam, Kanaka Sai Ram; Hunter, Keith D.; Radhakrishnan, Raghu (Clinical epigenetics, 2025)
The hypothesis that aberrant expression of homeobox (HOX) transcription factors contributes to oral cancer progression is gaining prominence. However, the mechanism of regulation involved in the clustered dysregulation of HOX clusters is not clearly known. Our findings revealed that HOXA and HOXB clusters showed significant locus-specific CpG methylation changes compared with the HOXC and HOXD clusters. The constitutively unmethylated regions identified in the HOXA1, HOXA11, HOXB5, HOXB6, HOXB9, HOXC5, HOXC10 and HOXC11 genes may be associated with open chromatin-mediated gene regulation. The methylation of CpG loci within the intron of HOXB9 may serve as a potential marker for distinguishing patients with premalignant and advanced oral tumors. HOXA5 and HOXC9 showed higher transcription factor-mediated interactions with neighboring HOX genes within and across the clusters. Additionally, HOXB9 and HOXC10 were predicted to directly regulate the G2-M checkpoint and hypoxia pathways. HOXA genes can be post-transcriptionally regulated through an antisense-mediated mechanism involving embedded HOX long noncoding RNAs (lncRNAs). Posterior HOX genes were more highly expressed than anterior HOX genes. The HOXC and HOXD cluster gene expression patterns were similar to those of the embedded lncRNAs. HOXA1, HOXC13 and HOXD10 were significantly correlated with the cancer hallmarks driving oral carcinogenesis. The functional consequence of HOX genes dysregulation was driven by diverse DNA and RNA epigenetic mechanisms affecting the transcriptional and post-transcriptional regulation contributing to the oral cancer progression.